Two new Cotasteromimina from Borneo (Coleoptera, Curculionidae: Molytinae) - Germann, Christoph (Zootaxa, 2021)
Based on material collected by canopy fogging in forests on Borneo, Obhylius arboricola gen. nov., sp. nov., and Seticotasteromimus brunomanseri sp. nov., the second species of this genus, are described. Further records of the type species of Seticotasteromimus Germann, 2013, S. jarawa Germann, 2013, are presented from Borneo, some 2700 km distant from the type locality on the Andaman Islands. Along with Seticotasteromimus, the new genus is best placed in the subtribe Cotasteromimina.